Papyrus British Museum 10056 Ergebnisse einer Neukollationierung und Anmerkungen zur inhaltlichen Auswertung im Rahmen der militärischen Ausbildung Amenophis’ II. - Gundacker, Roman (2017)
Papyrus British Museum 10056 is well known as a source for information on the history of New Kingdom economy and on shipbuilding. The present article, however, aims at evaluating this important papyrus in the context of chronology, of the education of princes in the Tuthmosid era and as a source for the localisation of Perunefer. In January 2014, the papyrus was collated in the British Museum, which allowed for the improvement of S.R.K. Glanville’s readings in a few instances. Perhaps the most important one concerns a much debated date on the verso, which, based on the suggestions made by S. Pasquali, now can be reconstructed as ‘regnal year 51, third month of winter, day 4’ (rnp.t-sp djjjwwj.t3bdhmt.nw prj.tswfdw). Accordingly, the papyrus must be assigned to Tuthmosis III, and there is no obstacle to the identification of the ‘king’s son and sem-priest Amenophis’ (s3-njswtsmJmnw-htp.w) as Amenophis II shortly before his inauguration as his father’s coregent. Further evaluation in the broader context of the princes’ education during the Tuthmosid era contributes to the knowledge of Amenophis II’s military training, which he received together with his ‘ foster brother Qenamun’ (sn nj mn') all throughout Egypt and which covered all branches of military service. The last stage of their education focussed on the navy and took place at the naval base and dockyard Perunefer, which most likely was located near Tell el-Dab‘a.
Keywords: Thutmosis III./Tuthmosis III; Amenophis II; Qenamun; Papyrus British Museum 10056; Prinzenerziehung/education of princes; Perunefer